A new regime of carbon counting: The practices and politics of accounting for everyday carbon through CO2e. (September 2015) - Ormond, Jim; Goodman, Michael K.
Highlights: Carbon is being counted and made knowable at mundane sites of everyday production and consumption. Central to these practices are a series of tools, models and databases (boundary objects). These enroll everyday actors from farmers to consumers and abstract and stabilize GHG emissions. Thereby establishing a new currency of 'everyday supply chain carbon'. Abstract: Inspired by the commercial desires of global brands and retailers to access the lucrative green consumer market, carbon is increasingly being counted and made knowable at the mundane sites of everyday production and consumption, from the carbon footprint of a plastic kitchen fork to that of an online bank account. Despite the challenges of counting and making commensurable the global warming impact of a myriad of biophysical and societal activities, this desire to communicate a product or service's carbon footprint has sparked complicated carbon calculative practices and enrolled actors at literally every node of multi-scaled and vastly complex global supply chains. Against this landscape, this paper critically analyzes the counting practices that create the 'e' in 'CO2 e'. It is shown that, central to these practices are a series of tools, models and databases which, in building upon previous work (Eden, 2012; Star and Griesemer, 1989 ) we conceptualize here as 'boundary objects'. By enrolling everyday actors from farmers to consumers, these objects abstract and stabilize greenhouse gas emissions from their messy material and social contexts into units of CO2 e which can then be translated along a product's supply chain, thereby establishing a new currency of 'everyday supply chain carbon'. However, in making all greenhouse gas-related practices commensurable and in enrolling and stabilizing the transfer of information between multiple actors these objects oversee a process of simplification reliant upon, and subject to, a multiplicity of approximations, assumptions, errors, discrepancies and/or omissions. Further the outcomes of these tools are subject to the politicized and commercial agendas of the worlds they attempt to link, with each boundary actor inscribing different meanings to a product's carbon footprint in accordance with their specific subjectivities, commercial desires and epistemic framings. It is therefore shown that how a boundary object transforms greenhouse gas emissions into units of CO2 e, is the outcome of distinct ideologies regarding 'what' a product's carbon footprint is and how it should be made legible. These politicized decisions, in turn, inform specific reduction activities and ultimately advance distinct, specific and increasingly durable transition pathways to a low carbon society.